Intravitreal bevacizumab (Avastin®) for macular oedema secondary to retinal vein occlusion: 12-month results of a prospective clinical trial. Issue 4 (15th December 2008) - Prager, F; Michels, S; Kriechbaum, K; Georgopoulos, M; Funk, M; Geitzenauer, W; Polak, K; Schmidt-Erfurth, U
Abstract : Aims: The aim of the study was to evaluate functional and anatomical changes after intravitreal bevacizumab (Avastin®) in eyes with persistent macular oedema secondary to branch retinal vein occlusion (BRVO) or central retinal vein occlusion (CRVO). Methods: Twenty-nine consecutive eyes with macular oedema secondary to BRVO (21 eyes) or CRVO (eight eyes) were included in a prospective clinical trial. Eyes were treated with three initial intravitreal bevacizumab injections of 1 mg at a monthly interval. Retreatment was based on central retinal thickness (CRT) based on optical coherence tomography. If continuous injections were indicated up to month 6, the dose was increased to 2.5 mg. Results: After 12 months of follow-up, mean visual acuity increased from 50 letters (20/100) at baseline to 66 letters (20/50 +1 ; +16 letters; p<0.001) at month 12 and CRT decreased from 558 μm at baseline to 309 μm at month 12 (−249 μm; p<0.001). Patients received a mean of eight out of 13 possible injections. No drug-related systemic or ocular side effects following intravitreal bevacizumab treatment were observed. Fluorescein angiography revealed no progression of avascular areas. Conclusions: Intravitreal therapy using bevacizumab appears to be a safe and effective treatment in patients with macular oedema secondary to retinal vein occlusion. However, the main limitations of this treatment modality are its short-term effectiveness and high recurrence rate.